Input factors and outcomes of pre-purchase dissonance - Mohd Radzol, Aifa Rozaini (2017)
This study addresses problems faced by parents regarding the choice of private tertiary education in Malaysia, for their children. Due to the intense competition to get a place in Malaysian Public Universities, parents turn to Private HEIs to pursue their children’s dreams. Private HEIs make enticing promises but the deliverables are not guaranteed; this, coupled with prohibitive costs often leaves parents in a dilemma which is known as Cognitive Dissonance. Previously, Cognitive Dissonance was believed to exist at the post-facto phase only. However, a recent study has shown that Cognitive Dissonance also exists at the ex-ante phase. Consequently, this research posits that if Cognitive Dissonance could be reduced at the ex-ante phase (i.e., Pre- Purchase Dissonance), it could increase buyers’ positive feelings towards a product; and, as a result, lead to a greater likelihood of purchase. Drawing on the Theory of Buyer Behavior, this study proposes a conceptual framework that examines the effects of antecedent and moderating variables on Pre-Purchase Dissonance vis., i) Brand Equity, Buyer Involvement and Advertising were independent variables, ii) Pre- Purchase Dissonance and Pre-Purchase Satisfaction were sequential mediating variables, iii) Buyer Expectation was the moderating variable, and iv) Word-Of-Mouth (WOM) was the moderating variable. Questionnaires were distributed to parents at education fairs and university open days in the Kuala Lumpur. This research adopted a purposive sampling technique; and 394 respondents completed the survey. Variance Based–Structural Equation Modelling (VB-SEM) was used to analyze the data (SmartPLS 3.0). The findings of this study suggest that Brand Equity and Buyer Involvement can reduce Pre-Purchase Dissonance; while advertising can induce Pre- Purchase Dissonance. Pre-Purchase Dissonance and Pre-Purchase Satisfaction were found to have a negative relationship. Pre-Purchase Satisfaction was also found to have a positive relationship with Purchase Intention. The findings also revealed that Pre-Purchase Dissonance and Pre-Purchase Satisfaction have a sequential mediating effect between Brand Equity and Advertising. This research found that WOM moderates the relationship between Pre-Purchase Dissonance and Pre-Purchase Satisfaction. These findings, suggest that Pre-Purchase Dissonance can be reduced at the ex-ante phase. Practically, marketers of Private HEIs should focus their marketing strategy on enhancing their Brand Equity, and promote parent Involvement to reduce Pre-Purchase Dissonance. In contrast, this research suggests that marketers should reconsider their Advertising strategy to attract parents because Advertising seems to create dissonance among parents.